Studying the potential ameliorative effect of biosynthesized selenium nanoparticles using epigallocatechin gallate against depression in rats - Alam-ElDein, Khaled M.; Faraag, Ahmed H. I.; El-Yamany, Nabil A.; Abdel Moneim, Ahmed E.; Abdelfattah, Mohamed S.; El-khadragy, Manal F.; Elmasry, Heba A. (Frontiers in Pharmacology, 2026)
IntroductionMajor depressive disorder (MDD) is a complex neuropsychiatric disorder with multifactorial origins involving oxidative stress, neuroinflammation, neurotransmitter imbalance, and HPA axis dysfunction. Conventional treatments are often limited by side effects and suboptimal efficacy, confirming the need for alternative therapies. This study investigates the antidepressant-like and neuroprotective potential of selenium nanoparticles biosynthesized using epigallocatechin gallate (SeNPs-EGCG) in a rat model of depression induced by chronic mild stress.MethodsSix groups of seven rats each were used in a model of depression caused by chronic unpredictable mild stress (CUMS): control, depressed, depressed treated with escitalopram, epigallocatechin gallate (EGCG), sodium selenite (Na2SeO3), and biosynthesised selenium nanoparticles capped with EGCG (SeNPs-EGCG). For 21 days, oral treatments were given. The open field test (OFT) and sucrose preference test (SPT) were used to measure depression-like behaviour. Oxidative stress markers, antioxidant enzymes, inflammatory cytokines, apoptotic proteins, monoamine neurotransmitters, corticosterone, BDNF, GFAP, and histopathological alterations were examined in prefrontal cortex tissue and serum.ResultsBehavioral assays demonstrated that SeNPs-EGCG significantly reversed depression-like behaviors, evidenced by increased sucrose preference and grooming frequency in the SeNPs-EGCG-treated group compared to the depressed group. Biochemically, SeNPs-EGCG restored antioxidant defense by increasing GSH, SOD, and CAT levels, while reducing lipid peroxidation to near-normal levels. Neuroinflammatory markers such as TNF-α, IL-1β, IL-8, and NF-κB were markedly downregulated in the SeNPs-EGCG group. Molecular results also showed a slowing down of proapoptotic signals (Bax and Caspase-3) and upregulation of anti-apoptotic Bcl-2 and neurotrophic factor BDNF. Importantly, SeNPs-EGCG modulated key monoamines, increasing serotonin and DA levels. Compared to both EGCG and sodium selenite controls, SeNPs-EGCG demonstrated superior efficacy, comparable to the standard antidepressant escitalopram. ConclusionThe results underscore the multi-targeted mechanism of SeNPs-EGCG and suggest its promising role as a novel nano-based therapeutic strategy for depression.